Efektivitas Penggunaan Anggaran Coronavirus Disease 2019 di Lembaga Pemasyarakatan Kelas IIB Kayu Agung - Novaria, Eva; Saddat, Muhammad Anwar (Program Studi Magister Ilmu Administrasi Publik STISIPOL Candradimuka, 2021)
Currently, Indonesia is facing a crisis caused by the Coronavirus disease 2019 outbreak, namely a crisis in the health sector and the economy, which has an impact on low state revenues and slo-wing economic growth. Knowing this, the government has taken various ways and efforts to re-duce or overcome the impact of the COVID-19 pandemic, namely by issuing various policies, one of which is Reocussing the health and economic budget. The Class IIB Kayu Agung Penitentiary is one of the Technical Implementation Units (UPT) within the Regional Office of the Ministry of Law and Human Rights in South Sumatra. Indonesia, then how to analyze the effectiveness of using the Corona Virus Disease 19 budget at the Class IIB Kayu Agung Penitentiary. The effectiveness measurement that is still widely used to measure effectiveness in terms of achieving goals is the effectiveness theory of Steers (1980:4-6), which says that the effectiveness of an organization depends on how far the organization achieves its goals/targets. The implementation of the use of the Corona Virus Disease 19 Budget at the Class IIB Kayu Agung Penitentiary is quite effective and Efficient, but there are still obstacles faced in its implementation.